1977
DOI: 10.1002/ana.410010106
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic polymyositis

Abstract: In 3 patients with subacute polymyositis, muscle biopsies were remarkable for showing abundant infiltration by eosinophils. In each case the inflammatory myopathy was part of a systemic illness known as the hypereosinophilic syndrome (HES). The systemic manifestations included eosinophilia, anemia, hypergammaglobulinemia, vascular involvement (subungual petechiae, livedo reticularis, Raynaud's phenomenon), skin rash and subcutaneous edema, pulmonary infiltrates and pleuritis, cardiac involvement (congestive he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
3

Year Published

1980
1980
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 21 publications
0
35
0
3
Order By: Relevance
“…The best-characterized examples in the FrenchAmerican-British classification of AML are M4Eo inv (16) Musculoskeletal N/A Arthritis, 79,80 effusions, 80 bursitis, 81 synovitis, 82 Raynaud phenomena, 83 digital necrosis, 84 polymyositis/myopathy 85,86 Renal N/A Acute renal failure with Charcot-Leyden crystalluria, 87 nephrotic syndrome, 88 immunotactoid glomerulopathy, 89 crescentic glomerulonephritis 90 Modified from Weller and Bubley 21 and from Brito-Babapulle 17 with permission from Elsevier. N/A indicates not available.…”
Section: Cytogenetic and Molecular Features Of Hematologic Malignancimentioning
confidence: 99%
“…The best-characterized examples in the FrenchAmerican-British classification of AML are M4Eo inv (16) Musculoskeletal N/A Arthritis, 79,80 effusions, 80 bursitis, 81 synovitis, 82 Raynaud phenomena, 83 digital necrosis, 84 polymyositis/myopathy 85,86 Renal N/A Acute renal failure with Charcot-Leyden crystalluria, 87 nephrotic syndrome, 88 immunotactoid glomerulopathy, 89 crescentic glomerulonephritis 90 Modified from Weller and Bubley 21 and from Brito-Babapulle 17 with permission from Elsevier. N/A indicates not available.…”
Section: Cytogenetic and Molecular Features Of Hematologic Malignancimentioning
confidence: 99%
“…3 recently described cases of eosinophilic polymyositis (Layzer et al, 1977) had more severe muscular involvement than reported in eosinophilic fasciitis, with pronounced proxi mal weakness and increased values of CPK. These cases had extensive visceral involvement with severe prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…Layzer et al [8] described three patients with symptoms of polymyositis and eosinophilic infiltration of the muscle tissue. These patients also had systemic manifestations such as heart failure, heart block, Raynaud's phenomenon, subungual splinter haemorrhages, skin rash and anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the other patient, who had no history of atopic illness, the eosinophil count ranged between 10 % and 21 %. Layzer et al [8] regarded eosinophilic polymyositis as part of the spectrum of IHES. Stark [9] described a case of eosinophilic polymyositis characterized by tender muscle swelling, creatine kinase elevation, and electromyographic features typical of polymyositis.…”
Section: Discussionmentioning
confidence: 99%